New Insights into Melanoma Tumor Syndromes - Sarem Rashid; Sameer Gupta; Shelley R. McCormick; Hensin Tsao (Elsevier, 2022)
Melanoma tumor syndromes (MTS) represent an important minority of familial melanoma cases. In these patients, the accumulation of sequence alterations in essential genes may prelude the risk of internal malignancies, in addition to melanoma. Although several host and environmental factors have been implicated in familial melanoma, the exact mechanisms of cancer predisposition-particularly in the context of mixed cancer syndromes-still remain unclear. In this paper, we review new insights into MTS and elucidate recent efforts that guide individualized prognostication and treatment for these diseases in the past quarter century.